2017
DOI: 10.1007/s00701-017-3262-5
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuropathy associated with an enlarging arachnoid cyst in Meckel’s cave: case report, management strategy and review of the literature

Abstract: We describe a rare case and novel management strategy of painful trigeminal neuropathy caused by an arachnoid cyst confined to Meckel's cave. A 57-year-old female presented with several years of progressive trigeminal pain and signs of trigeminal deafferentation, including sensory loss, corneal anesthesia and mastication muscle atrophy. Medical treatment with carbamazepine provided partial and temporary pain control. Surgical treatment was eventually performed by aspiration of the arachnoid cyst through the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The secondary ones are less common and are associated with neoplasms, infections, bleeding, trauma or surgery. 2,3 Depending on their location and size, arachnoid cysts may become symptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The secondary ones are less common and are associated with neoplasms, infections, bleeding, trauma or surgery. 2,3 Depending on their location and size, arachnoid cysts may become symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, we found only eight cases reported as MC arachnoid cyst (►Table 1). 2,[5][6][7][8][9][10][11] The average age of the patients was 41 years oldwith a range from 1 to 58 years oldand there was a female predominance (5 out of 8). The most affected side was the right side (five out of eight).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Messerer et al reported contamination of sample tissue with fat, CSF or blood, leading to diagnostic difficulties [83]. Drainage of arachnoid cysts, however, has been reported as feasible [21]. In the further course, an endoscopic transforamen ovale approach and observation of Meckel's cave were reported [48].…”
Section: Percutaneousmentioning
confidence: 99%
“…Neuroendocrine carcinoma [63] Adenoid cystic carcinoma [5] Malignant melanotic schwannoma [23,61,101] Squamous cell carcinoma [63] Adenocarcinoma [63] Inflammatory Sarcoidosis [19,69] Amyloidoma [22,24,28] IgG4 disease [63] Necrotizing granulomatous inflammation [63] Inflammatory pseudotumor [63] Hematologic malignancies Primary malignant lymphoma [26] Multiple myeloma [32] NK/T lymphoma [63] Diffuse B-cell lymphoma* Plasmacytoma [63] Marginal zone lymphoma [63] Chronic eosinophilic leukemia [63] Lymphoplasmocytic lymphoma [63] Non-Hodgkin lymphoma [63] Cystic Arachnoid cyst [5,21,34,61,64] Epidermoid cyst [17,29] Meningoceles [102] *Illustrative case report presented in this article should, however, be seen as complementary and not competitive [73], since each one of them carries its own risks and advantages. Even though newly described endoscopic approaches appear promising, clinical experiences remain to be reported and an advanced anatomical knowledge of the neurovascular array within and surrounding the skull base is of utmost priority to assure safety during and after procedures.…”
Section: ] Metastaticmentioning
confidence: 99%